Catalyst for Decomposing Ammonia Having Enhanced Stability and Method for Generating Hydrogen Using the Same

KR103022342B1Active Publication Date: 2026-09-18KOREA RES INST OF CHEM TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020240009997
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-01-23
Publication Date
2026-09-18
Estimated Expiration
2044-01-23

Smart Images

  • Figure 112024008695446-PAT00008_ABST
    Figure 112024008695446-PAT00008_ABST
Patent Text Reader

Abstract

The present invention relates to a catalyst for an ammonia decomposition reaction and a method for producing hydrogen using the same. More specifically, the catalyst for an ammonia decomposition reaction comprises a cobalt and molybdenum composite nitride containing cesium and cerium, thereby exhibiting excellent catalytic activity in the ammonia decomposition reaction to improve the ammonia conversion rate, and having excellent long-term stability as the activity does not significantly decrease even after high temperatures and prolonged reaction times. The invention also relates to a method for producing hydrogen using the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a catalyst for an ammonia decomposition reaction and a method for producing hydrogen using the same. More specifically, the invention relates to a catalyst for an ammonia decomposition reaction with improved catalyst stability, which can improve the ammonia conversion rate in the ammonia decomposition reaction and suppress catalyst deactivation to exhibit long-term stability, and a method for producing hydrogen using the same. Background Technology

[0002] With climate change intensifying recently, hydrogen energy is garnering global attention as an eco-friendly fuel to replace fossil fuels. To commercialize hydrogen energy, the development of technologies for safely and efficiently storing and transporting hydrogen is crucial. While there are various methods for storing hydrogen, the use of hydrogen storage materials capable of reversibly storing and releasing hydrogen is expected to serve as a hydrogen storage medium for fuel cell vehicles.

[0003] One method for efficiently storing and transporting hydrogen is to use ammonia as a storage and supply source. Since the process of ammonia decomposing into hydrogen and nitrogen is endothermic, energy is required to obtain the products. Conventional catalytic decomposition reactions require a large amount of heat to produce a useful amount of hydrogen gas, resulting in high costs for hydrogen production.

[0004] 2NH3→ 3H2+ N2(endothermic reaction)...(1)

[0005] Catalysts for ammonia decomposition reactions are catalysts that decompose ammonia into nitrogen and hydrogen. Conventionally, when attempting to obtain high-purity hydrogen using ammonia decomposition catalysts proposed so far, the conversion rate was low, or catalysts that increased reaction activity to raise the conversion rate tended to show an excessive decrease in catalytic activity over time.

[0006] In accordance with these circumstances, the present invention aims to present a new ammonia decomposition catalyst that has a high conversion rate from ammonia to nitrogen and hydrogen while simultaneously possessing high stability.

[0007] As prior art, European Patent Publication No. 2612706 first relates to an ammonia oxidation / decomposition catalyst, and more specifically, discloses a catalyst capable of reducing hydrogen production costs by utilizing the heat generated in the ammonia oxidation reaction for the ammonia decomposition reaction, comprising the precious metal ruthenium as a catalytic active component and lanthanum oxide and / or cerium oxide as a catalyst support.

[0008] In addition, Japanese Patent Publication No. 2011-224556 relates to a catalyst for ammonia decomposition, a method for manufacturing the catalyst, and a method for producing hydrogen using the catalyst. More specifically, the technology relates to a catalyst that exhibits high activity for an ammonia decomposition reaction and can efficiently decompose ammonia into hydrogen and nitrogen, wherein the catalyst comprises a Group 8 metal to which ruthenium belongs as a catalyst component and lanthanum oxide and / or cerium oxide as a catalyst support component.

[0009] However, these catalysts are precious metal catalysts based on ruthenium, and their application in large-scale processes was limited due to their rarity and high cost.

[0010] Accordingly, while researching non-precious metal catalysts for ammonia decomposition reactions, the inventors confirmed that a catalyst for ammonia decomposition reaction comprising a new type of complex nitride containing cerium and cesium in a cobalt and molybdenum complex nitride exhibits superior catalytic activity compared to existing catalysts and demonstrates long-term stability by maintaining activity even after a long period of time, thereby completing the present invention. Prior art literature

[0011] European Patent Publication No. 2612706 (Publication Date: July 10, 2013) Japanese Patent Publication No. 2011-224556 (Publication Date: November 10, 2011) The problem to be solved

[0012] The main objective of the present invention is to solve the aforementioned problems by providing a catalyst for an ammonia decomposition reaction that has high activity in the ammonia decomposition reaction and can maintain activity over a long period, and a method for producing hydrogen using the same. means of solving the problem

[0013] To achieve the above objectives, one embodiment of the present invention provides a catalyst for an ammonia decomposition reaction with improved catalytic stability, characterized by containing cesium and cerium in a cobalt and molybdenum composite nitride.

[0014] In a preferred embodiment of the present invention, the cesium may be characterized as being contained in an amount of 0.001 mole to 0.05 mole per 1 mole of cobalt and molybdenum complex nitride.

[0015] In a preferred embodiment of the present invention, the cerium may be characterized as being contained in an amount of 0.01 mol to 0.4 mol per 1 mol of cobalt and molybdenum complex nitride.

[0016] In a preferred embodiment of the present invention, the cobalt and molybdenum composite nitride may be characterized in that the cobalt is contained in an amount of 0.5 moles to 1.5 moles per mole of molybdenum.

[0017] Another embodiment of the present invention provides a method for producing a catalyst for an ammonia decomposition reaction with improved catalyst stability, characterized by comprising: (a) mixing a cobalt precursor, a molybdenum precursor, a cesium precursor, and a cerium precursor; (b) drying the mixture from step (a); and (c) nitriding the mixture dried in step (b) with a nitrogen source to produce a cobalt and molybdenum composite nitride containing cesium and cerium.

[0018] In another preferred embodiment of the present invention, the method may be characterized by including a step of aging the mixture of step (a) after step (a).

[0019] In another preferred embodiment of the present invention, the aging may be characterized by being performed at 25°C to 100°C for 0.1 hours to 10 hours.

[0020] In another preferred embodiment of the present invention, the step (b) may further include a step of firing after drying.

[0021] In another preferred embodiment of the present invention, the sintering may be characterized by performing a first sintering at 100 ℃ to 400 ℃, followed by a second sintering at 400 ℃ to 700 ℃.

[0022] In another preferred embodiment of the present invention, step (a) may be characterized by mixing a cobalt precursor, a molybdenum precursor, a cesium precursor, and a cerium precursor using solvent-deficient milling.

[0023] In another preferred embodiment of the present invention, the nitriding treatment of step (c) may be characterized by being performed at 600 ℃ to 800 ℃.

[0024] In another preferred embodiment of the present invention, the nitrogen source may be characterized as being one or more selected from the group consisting of ammonia, sodium cyanide, potassium cyanide, urea, and melamine.

[0025] Another embodiment of the present invention provides a method for producing hydrogen from ammonia, characterized by contacting a cobalt and molybdenum complex nitride containing cesium and cerium with a gas containing ammonia to cause an ammonia decomposition reaction.

[0026] In another preferred embodiment of the present invention, the contact between the ammonia and the cobalt and molybdenum complex nitride containing cesium and cerium may be characterized by being performed at 300°C to 600°C. Effects of the invention

[0027] The catalyst for an ammonia decomposition reaction according to the present invention contains cesium and cerium in a cobalt and molybdenum complex nitride, thereby exhibiting excellent catalytic activity in the ammonia decomposition reaction. Furthermore, since the deactivation of the catalyst is suppressed even after high temperatures and prolonged reaction times, the activity does not significantly decrease, resulting in excellent long-term stability of the catalyst.

[0028] In addition, the method for manufacturing a catalyst for an ammonia decomposition reaction according to the present invention minimizes the use of solvent, thereby reducing the time and cost required to dry the solvent and facilitating mass production of the catalyst. Furthermore, by manufacturing the catalyst using solvent-deficient milling, which minimizes the reduction in catalyst performance, it has the effect of enabling mass production on a commercial scale without a decrease in catalyst activity. Brief explanation of the drawing

[0029] FIG. 1 is a graph showing the results of measuring the ammonia conversion rate of catalysts prepared in Preparation Examples 1 to 7 according to the present invention, FIG. 1(a) is a graph showing the results of measuring the ammonia conversion rate of catalysts prepared in Preparation Examples 1 to 4, and FIG. 1(b) is a graph showing the results of measuring the ammonia conversion rate of catalysts prepared in Preparation Examples 5 to 7. Figure 2 is a graph showing the results of measuring the ammonia conversion rate of the catalysts prepared in Preparation Examples 5 and 8 to 11 according to the present invention. FIG. 3 is a graph showing the results of measuring the ammonia conversion rate of catalysts prepared in Preparation Examples 5 and 12 to 16 according to the present invention, FIG. 3(a) is a graph showing the results of measuring the ammonia conversion rate of catalysts prepared in Preparation Examples 5 and 12 to 15, and FIG. 3(b) is a graph showing the results of measuring the ammonia conversion rate of catalysts prepared in Preparation Examples 5 and 16. FIG. 4 is a graph showing the results of measuring the ammonia conversion rate of catalysts prepared in Preparation Examples 5 and 17 to 24 according to the present invention, FIG. 4(a) is a graph showing the results of measuring the ammonia conversion rate of catalysts prepared in Preparation Examples 5, 17 to 20 and 23, and FIG. 4(b) is a graph showing the results of measuring the ammonia conversion rate of catalysts prepared in Preparation Examples 5 and 21 to 24. Figure 5 is a graph showing the results of measuring the ammonia conversion rate of the catalysts prepared in Preparation Examples 1, 5, 23, and 24 according to the present invention. FIG. 6 is a graph showing the results of measuring the long-term stability of catalysts prepared in Preparation Examples 1, 5, 23, and 24 according to the present invention, FIG. 6(a) is a graph showing the ammonia conversion rate according to reaction time, and FIG. 6(b) is X according to reaction time. NH3 / X 0 NH3 This is a graph measuring . Specific details for implementing the invention

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by a skilled expert in the art to which the present invention pertains. In general, the nomenclature used herein is well known and commonly used in the art.

[0031] Terms such as “comprising,” “including,” or “having” as used in this specification refer to the existence of the features, figures, steps, actions, components, parts, or combinations thereof described in the specification, and do not exclude the possibility that other unmentioned features, figures, steps, actions, components, parts, or combinations thereof may exist or be added.

[0032] The reactions and mixing described below may be carried out at room temperature and pressure unless otherwise specified, and may be performed under normal reaction and mixing conditions without any additional measures. However, the interpretation must not deviate from what is clear to those skilled in the art.

[0033] In one aspect, the present invention provides a catalyst for an ammonia decomposition reaction with improved catalytic stability, characterized by containing cesium and cerium in a cobalt and molybdenum composite nitride.

[0034] Hereinafter, a catalyst for an ammonia decomposition reaction according to the present invention will be described in detail.

[0035] The catalyst for an ammonia decomposition reaction according to the present invention is characterized by containing cesium and cerium in a cobalt and molybdenum complex nitride. When used for an ammonia decomposition reaction, it is more economical than conventional precious metal catalysts, exhibits superior ammonia decomposition reaction efficiency compared to conventional non-metal catalysts, and demonstrates long-term stability of the catalyst by suppressing catalyst deactivation over time even at high temperatures and for extended periods.

[0036] In the catalyst for an ammonia decomposition reaction according to the present invention, the cobalt and molybdenum composite nitride is a nitride containing cobalt and molybdenum, wherein, for every 1 mole of molybdenum, cobalt may be contained in an amount of 0.5 moles to 1.5 moles, preferably 0.8 moles to 1.2 moles. In the cobalt and molybdenum composite nitride, the maximum amount of cobalt and molybdenum composite nitride can be formed by satisfying the aforementioned content ranges for the cobalt and molybdenum.

[0037] In addition, the cesium contained in the above cobalt and molybdenum complex nitride may be present in an amount of 0.001 mole to 0.05 mole, preferably 0.004 mole to 0.015 mole per 1 mole of the cobalt and molybdenum complex nitride.

[0038] If the above cesium content is less than 0.001 moles per mole of cobalt and molybdenum complex nitride, the effect of the co-catalyst may be insufficient due to the small amount of added cesium, and if it exceeds 0.05 moles, the excessive cesium may cover the surface of the catalyst, thereby blocking the exposure of the active material and the pores of the catalyst.

[0039] In addition, cerium contained in the above cobalt and molybdenum composite nitride plays a positive role in activity and thermal stability as a co-catalyst, and may be included in an amount of 0.01 mol to 0.4 mol, preferably 0.05 mol to 0.20 mol, per 1 mol of cobalt and molybdenum composite nitride.

[0040] If the cerium content is less than 0.001 moles per mole of cobalt and molybdenum complex nitride, the effect of the co-catalyst may be insufficient due to the small amount of added cerium, and if it exceeds 0.4 moles, the excessive cesium may cover the surface of the catalyst, thereby blocking the exposure of the active material and the pores of the catalyst.

[0041] In addition, in another aspect, the present invention provides a method for producing a catalyst for an ammonia decomposition reaction with improved catalyst stability, characterized by comprising: (a) a step of mixing a cobalt precursor, a molybdenum precursor, a cesium precursor, and a cerium precursor; (b) a step of drying the mixture of step (a); and (c) a step of nitriding the mixture dried in step (b) with a nitrogen source to produce a cobalt and molybdenum composite nitride containing cesium and cerium.

[0042] The method for manufacturing a catalyst for an ammonia decomposition reaction according to the present invention will be described in detail step by step below.

[0043] Step (a) above is a step of mixing a cobalt precursor, a molybdenum precursor, a cesium precursor, and a cerium precursor to obtain a mixture.

[0044] The above step is a step of uniformly mixing a cobalt precursor, a molybdenum precursor, a cesium precursor, and a cerium precursor. Specifically, a mixture of the cobalt precursor, molybdenum precursor, cesium precursor, and cerium precursor can be obtained by using solvent-deficient milling or by dissolving the cobalt precursor, molybdenum precursor, cesium precursor, and cerium precursor in a solvent.

[0045] In one embodiment, the solvent-deficient milling is a mixing method that is solvent-free or uses a small amount of solvent, and can be performed using a mixing device such as a ball mill, planetary mill, stirred ball mill, or vibrating mill that uses chemically inert beads, for example. At this time, to maximize the mixing effect, a small amount of solvent capable of dissolving the precursor, such as water, methanol, and ethanol, may be optionally added.

[0046] In one embodiment, when mixing precursors using solvent-deficient milling according to the present invention, milling can be performed for 6 to 72 hours at a rotational speed of 100 rpm to 1000 rpm.

[0047] Mixing such cobalt, molybdenum, cesium, and cerium precursors using solvent-deficient milling can reduce the cost of solvent removal required in subsequent processes by minimizing solvent usage, and can achieve the effect of minimizing the degradation of catalyst performance while facilitating the production of large quantities of catalysts.

[0048] Meanwhile, in another embodiment, the solvent mixture of the cobalt precursor, molybdenum precursor, cesium precursor, and cerium precursor may be prepared by adding the required amounts to individual solvents and mixing these solutions to obtain a mixture, or the measured amounts of the cobalt precursor, molybdenum precursor, cesium precursor, and cerium precursor may all be added to a single solvent to obtain a mixture of the cobalt precursor, molybdenum precursor, cesium precursor, and cerium precursor. In this case, the solvent is not limited to any solvent capable of dissolving the precursors, and is preferably water.

[0049] The above cobalt precursor, molybdenum precursor, cesium precursor, and cerium precursor may be one or more selected from the group comprising organic and inorganic compounds containing each metal element (cobalt, molybdenum, cesium, and cerium) or ion, and specifically may be chlorides, hydrates, nitrides, acetylacetonates, iodides, etc. of each metal, and as a preferred embodiment, may be in the form of nitrides and hydrates, but are not limited thereto.

[0050] As a specific example, cobalt precursors may be cobalt nitrate [Co(NO3)2], cobalt nitrate hydrate [Co(NO3)2ㆍxH2O], cobalt chloride (CoCl2), etc., and molybdenum precursors may be ammonium molybdate [(NH4)2MoO4], ammonium molybdate hydrate [(NH4)6Mo7O 24 It may be 4H2O, sodium molybdate (Na2MoO4), etc.

[0051] In addition, as a specific example, the cesium precursor may be cesium nitrate (CsNO3), cesium chloride (CsCl), etc., and the cerium precursor may be cerium nitrate [Ce(NO3)3], cerium nitrate hydrate [Ce(NO3)3ㆍxH2O], etc.

[0052] Subsequently, the mixture obtained in step (a) above may include a step of aging prior to the drying step described later so that the catalyst composition and crystallization can be effectively achieved.

[0053] The above aging can be performed using various mixers and stirrers to ensure uniform mixing, and can be performed at 25°C to 100°C, preferably 70°C to 90°C, for 0.1 hours to 10 hours.

[0054] If the above aging temperature is below 25 ℃, smooth mixing and nucleation rates are slow, and CoMoO, the main component of the catalyst x Problems may arise where compound formation is not smooth, and if the temperature exceeds 100 ℃, the nucleation rate accelerates, CoMoO x A problem may arise where the activity of the catalyst is reduced due to the formation of large compound particles. In addition, if the aging time is less than 0.1 hours, CoMoO due to the short aging time x Problems may arise where the compound is not sufficiently formed, and if it exceeds 10 hours, smooth CoMoO xWhile the formation of compounds can be expected, unnecessary economic issues may arise during the catalyst manufacturing stage due to the long aging time.

[0055] Next, step (b) is a step of drying the aforementioned mixture, wherein the drying can be performed at 25°C to 150°C, preferably 90°C to 120°C, after evaporating the solvent contained in the mixture. If the drying temperature is 90°C or higher, drying can be performed effectively, and if it is 120°C or lower, costs can be saved relatively. Additionally, the drying time is preferably controlled within 24 hours according to the drying state of the mixture, but may be extended beyond that if necessary.

[0056] Subsequently, the dried mixture may be further calcined in an oxidizing atmosphere, such as air or an oxygen-containing mixed gas, at a temperature of 200°C to 800°C, preferably 350°C to 600°C. If the calcination temperature is 200°C or higher, impurities can be sufficiently removed, thereby improving the ammonia decomposition efficiency; if the temperature is maintained at 800°C or lower, the possibility of a decrease in catalyst performance due to sintering can be reduced. Additionally, since the calcination time varies depending on the amount of material to be calcined and the calcination apparatus, it may be difficult to express it quantitatively; therefore, it is preferable to determine the calcination completion time based on the state of the calcined material. Nevertheless, if the calcination time is to be limited, it can be performed for 30 hours or less.

[0057] In addition, the above-mentioned calcination may be performed within the aforementioned temperature range, but the calcination step may be divided into a first calcination and a second calcination to prevent rapid shrinkage and structural changes of various complex oxides (cesium, cerium, cobalt, and molybdenum). At this time, the first calcination may be performed at 100 ℃ to 400 ℃, and the second calcination may be performed at 400 ℃ to 700 ℃ after the first calcination.

[0058] If calcination is performed separately by temperature within the aforementioned temperature range, it is possible to prevent the rapid shrinkage of the complex oxide that occurs as impurities present in the mixture escape due to rapid temperature changes, which is desirable for increasing and maintaining the specific surface area of ​​the catalyst.

[0059] Subsequently, step (c) is a step of nitriding treatment to maximize the ammonia decomposition reaction activity of cobalt and molybdenum, which are the main active components of the mixture dried in step (b), and the nitriding treatment can be performed under a nitrogen source at 300 ℃ to 800 ℃, preferably 600 ℃ to 750 ℃ ​​for 0.1 hours to 8 hours.

[0060] If the above nitriding treatment is performed at a temperature below 300°C, a sufficient nitriding effect cannot be expected, and if performed at a temperature exceeding 800°C, a problem may arise in which the efficiency of the ammonia decomposition reaction is reduced due to a decrease in the specific surface area caused by the aggregation of the catalyst material. In addition, since the nitriding treatment time varies depending on the amount of reactants, it may be difficult to express it quantitatively, so it is desirable to judge based on the state of the nitrided nitride. Nevertheless, if the calcination time is to be limited, it can be performed for 1 to 4 hours.

[0061] At this time, any nitrogen source used in the above nitriding treatment may be used without limitation as long as it is a compound containing nitrogen atoms commonly used in the field, such as ammonia, urea, melamine, etc.

[0062] In another aspect, the present invention provides a method for producing hydrogen from ammonia using the aforementioned catalyst for an ammonia decomposition reaction.

[0063] Specifically, the method for producing hydrogen according to the present invention can produce hydrogen by an ammonia decomposition reaction by contacting a cobalt and molybdenum complex nitride containing cesium and cerium, i.e., the aforementioned catalyst for an ammonia decomposition reaction, with a gas containing ammonia.

[0064] The above-mentioned ammonia-containing gas is not particularly limited, but may include not only ammonia gas or ammonia-containing gas, but also a gas containing substances that produce ammonia through thermal decomposition, such as urea.

[0065] In addition, the ammonia-containing gas may contain other components as long as it does not become a catalyst poison. The reaction temperature is preferably 300 ℃ to 600 ℃. The reaction pressure may be 0.002 MPa to 2 MPa in absolute pressure, more preferably 0.004 MPa to 1 MPa.

[0066] The above catalyst for the ammonia decomposition reaction exhibits an ammonia conversion rate of 50% or more at a temperature in the range of 450 ℃ to 550 ℃, and specifically, can exhibit an ammonia conversion rate of 80% or more at a temperature in the range of 500 ℃ to 550 ℃.

[0067] The present invention will be explained in more detail below through specific embodiments. The following embodiments are merely examples to aid in understanding the present invention and do not limit the scope of the present invention.

[0068] <Preparation Example 1 : CoMoO x -N catalyst>

[0069] 2.5 g of Co(NO3)2ㆍ6H2O and (NH4)6Mo7O 24 1.51 g of ⁴H₂O was dissolved in 100 ml of deionized water to obtain a homogeneous mixture, and the obtained mixture was aged at 80 °C for 1 hour while stirring. The moisture in the aged mixture was evaporated using a rotary evaporator, and the mixture was dried at 100 °C for 20 hours. Subsequently, the dried mixture was calcined for the first time at 350 °C for 15 hours, followed by a second calcination at 600 °C for 5 hours. The calcined product was nitrided under ammonia gas at 700 °C for 3 hours to produce CoMoO x -N catalyst was prepared. At this time, the above CoMoO x - In catalyst notation, the subscript indicates the moles of the corresponding component.

[0070] <Preparation Examples 2 to 4: CoMoO x -N catalyst>

[0071] The catalyst was prepared in the same manner as in Preparation Example 1, but with the aging time changed to the time listed in Table 1, and CoMoO x -N catalysts were prepared separately.

[0072] <Preparation Example 5: Cs 0.007 Ce 0.1 -CoMoO x -N catalyst>

[0073] 2.5 g of Co(NO3)2ㆍ6H2O and (NH4)6Mo7O by the method of Preparation Example 5 241.51 g of ·4H2O, 0.38 g of Ce(NO3)3·6H2O, and 0.011 g of CsNO3 were dissolved in 100 ml of deionized water to obtain a homogeneous mixture, and the obtained mixture was aged at 80 °C for 3 hours while stirring. The moisture in the aged mixture was evaporated using a rotary evaporator, and the mixture was dried at 100 °C for 20 hours. Subsequently, the dried mixture was calcined for the first time at 350 °C for 15 hours, followed by a second calcination at 600 °C for 5 hours. The calcined product was nitrided under ammonia gas at 700 °C for 3 hours to obtain Cs 0.007 Ce 0.1 -CoMoO x -N catalyst was prepared. At this time, the above Cs 0.007 Ce 0.1 -CoMoO x - In catalyst notation, the subscript indicates the moles of the corresponding component.

[0074] <Preparation Examples 6 to 10: Cs 0.007 Ce 0.1 -CoMoO x -N catalyst >

[0075] Cs in the same manner as in Preparation Example 5 0.007 Ce 0.1 -CoMoO x Prepare an -N catalyst, but change the prepared catalyst to the conditions in Table 1 below to Cs 0.007 Ce 0.1 -CoMoO x -N catalyst was prepared.

[0076] <Preparation Example 11 : Cs 0.007 Ce 0.1 -CoMoO x -N catalyst >

[0077] Cs in the same manner as in Preparation Example 5 0.007 Ce 0.1 -CoMoO xPrepare an -N catalyst, excluding the calcination step, and dry at 100 ℃ for 20 hours, then perform only the nitriding treatment step to obtain Cs 0.007 Ce 0.1 -CoMoO x -N catalyst was prepared.

[0078] <Preparation Examples 12 to 16: Cs 0.007 Ce 0.1 -CoMoO x -N catalyst >

[0079] Cs in the same manner as in Preparation Example 5 0.007 Ce 0.1 -CoMoO x Prepare an -N catalyst, but change the conditions to those in Table 1 below to Cs 0.007 Ce 0.1 -CoMoO x -N catalyst was prepared.

[0080] [Table 1]

[0081]

[0082] <Preparation Example 17 : Cs 0.007 Ce 0.01 -CoMoO x -N catalyst>

[0083] A catalyst was prepared in the same manner as in Preparation Example 5, except that 0.037 g of Ce(NO3)3·6H2O was mixed instead of 0.38 g of Ce(NO3)3·6H2O to obtain Cs 0.007 Ce 0.01 -CoMoO x -N catalyst was prepared. At this time, the above Cs 0.007 Ce 0.01 -CoMoO x - In catalyst notation, the subscript indicates the moles of the corresponding component.

[0084] <Preparation Example 18 : Cs 0.007 Ce 0.05 -CoMoO x -N catalyst>

[0085] A catalyst was prepared in the same manner as in Preparation Example 5, except that 0.186 g of Ce(NO3)3·6H2O was mixed instead of 0.38 g of Ce(NO3)3·6H2O to obtain Cs 0.007 Ce 0.05 -CoMoO x -N catalyst was prepared. At this time, the above Cs 0.007 Ce 0.05 -CoMoO x - In catalyst notation, the subscript indicates the moles of the corresponding component.

[0086] <Preparation Example 19 : Cs 0.007 Ce 0.20 -CoMoO x -N catalyst>

[0087] A catalyst was prepared in the same manner as in Preparation Example 5, except that 0.745 g of Ce(NO3)3·6H2O was mixed instead of 0.38 g of Ce(NO3)3·6H2O to obtain Cs 0.007 Ce 0.20 -CoMoO x -N catalyst was prepared. At this time, the above Cs 0.007 Ce 0.20 -CoMoO x - In catalyst notation, the subscript indicates the moles of the corresponding component.

[0088] <Preparation Example 20 : Cs 0.007 Ce 0.50 -CoMoO x -N catalyst>

[0089] A catalyst was prepared in the same manner as in Preparation Example 5, except that 1.86 g of Ce(NO3)3·6H2O was mixed instead of 0.38 g of Ce(NO3)3·6H2O to obtain Cs 0.007 Ce 0.50 -CoMoO x -N catalyst was prepared. At this time, the above Cs 0.007 Ce 0.50 -CoMoO x - In catalyst notation, the subscript indicates the moles of the corresponding component.

[0090] <Preparation Example 21 : Cs 0.004 Ce 0.10 -CoMoO x -N catalyst>

[0091] The catalyst was prepared in the same manner as in Preparation Example 5, except that 0.006 g of CsNO3 was mixed instead of 0.011 g of CsNO3, and Cs 0.004 Ce 0.10 -CoMoO x -N catalyst was prepared. At this time, the above Cs 0.004 Ce 0.50 -CoMoO x - In catalyst notation, the subscript indicates the moles of the corresponding component.

[0092] <Preparation Example 22 : Cs 0.015 Ce 0.10 -CoMoO x -N catalyst>

[0093] The catalyst was prepared in the same manner as in Preparation Example 5, except that 0.023 g of CsNO3 was mixed instead of 0.011 g of CsNO3, and Cs 0.015 Ce 0.10 -CoMoO x -N catalyst was prepared. At this time, the above Cs 0.015 Ce 0.10 -CoMoO x - In catalyst notation, the subscript indicates the moles of the corresponding component.

[0094] <Preparation Example 23 : Cs 0.007 -CoMoO x -N catalyst>

[0095] A catalyst was prepared by the same method as in Preparation Example 5, but without adding a cerium precursor, and Cs 0.007 -CoMoO x -N catalyst was prepared. At this time, the above Cs 0.007 -CoMoO x - In catalyst notation, the subscript indicates the moles of the corresponding component.

[0096] <Preparation Example 24 : Ce 0.10 -CoMoO x -N catalyst>

[0097] A catalyst was prepared using the same method as in Preparation Example 5, but without adding a cesium precursor, to produce Ce 0.10 -CoMoO x -N catalyst was prepared. At this time, the above Ce 0.10 -CoMoO x - In catalyst notation, the subscript indicates the moles of the corresponding component.

[0098] <Preparation Example 25 : Cs 0.007 Ce 0.1 -CoMoO x -N catalyst>

[0099] Co(NO3)2ㆍ6H2O 14.85 g, (NH4)6Mo7O 24 4H2O 8.83 g, Ce(NO3)3ㆍ6H2O 2.19 g and CsNO3 0.069 g was dissolved in 200 ml of deionized water to obtain a homogeneous mixture, and the obtained mixture was aged at 80 °C for 3 hours while stirring. The moisture in the aged mixture was evaporated using a rotary evaporator, and the mixture was dried at 100 °C for 20 hours. Subsequently, the dried mixture was calcined for the first time at 350 °C for 15 hours, followed by a second calcination at 600 °C for 5 hours. The calcined product was nitrided under ammonia gas at 700 °C for 3 hours to obtain Cs 0.007 Ce 0.1 -CoMoO x -N catalyst was prepared. At this time, the above Cs 0.007 Ce 0.1 -CoMoO x - In catalyst notation, the subscript indicates the moles of the corresponding component.

[0100] <Preparation Example 26 : Cs 0.007 Ce 0.1 -CoMoO x -N catalyst>

[0101] Co(NO3)2ㆍ6H2O 29.70 g, (NH4)6Mo7O 24 4H2O 17.66 g, Ce(NO3)3ㆍ6H2O 4.39 g and CsNO3 0.1378 g was dissolved in 300 ml of deionized water to obtain a homogeneous mixture, and the obtained mixture was aged at 80 °C for 3 hours while stirring. The moisture in the aged mixture was evaporated using a rotary evaporator, and the mixture was dried at 100 °C for 20 hours. Subsequently, the dried mixture was calcined for the first time at 350 °C for 15 hours, followed by a second calcination at 600 °C for 5 hours. The calcined product was nitrided under ammonia gas at 700 °C for 3 hours to obtain Cs 0.007 Ce 0.1 -CoMoO x -N catalyst was prepared. At this time, the above Cs 0.007 Ce 0.1 -CoMoO x - In catalyst notation, the subscript indicates the moles of the corresponding component.

[0102] <Preparation Example 27 : Cs 0.007 Ce 0.1 -CoMoO x -N catalyst>

[0103] Co(NO3)2ㆍ6H2O 14.85 g, (NH4)6Mo7O 24 4H2O 8.83 g, Ce(NO3)3ㆍ6H2O 2.19 g and CsNO3 0.0689 g was dissolved in 10 ml of deionized water to obtain a homogeneous mixture, and then the obtained mixture was fed into a ball milling device (LM-BS750, LK LABKOREA) and ball milled at a rotational speed of 350 rpm for 24 hours. The ball-milled mixture was vacuum dried at 150 ℃ for 24 hours, and subsequently, the dried mixture was calcined at 600 ℃ for 5 hours. The calcined product was nitrided under ammonia gas at 700 ℃ for 3 hours to obtain Cs 0.007 Ce 0.1 -CoMoO x -N catalyst was prepared. At this time, the above Cs 0.007 Ce 0.1 -CoMoO x - In catalyst notation, the subscript indicates the moles of the corresponding component.

[0104] <Preparation Example 28 : Cs 0.007 Ce 0.1 -CoMoO x -N catalyst>

[0105] Co(NO3)2ㆍ6H2O 29.70 g, (NH4)6Mo7O 24 4H2O 17.66 g, Ce(NO3)3ㆍ6H2O 4.39 g and CsNO3 0.1378 g was dissolved in 20 ml of deionized water to obtain a homogeneous mixture, and then the obtained mixture was fed into a ball milling device (LM-BS750, LK LABKOREA) and ball milled at a rotational speed of 350 rpm for 24 hours. The ball-milled mixture was vacuum dried at 150 ℃ for 24 hours, and subsequently, the dried mixture was calcined at 600 ℃ for 5 hours. The calcined product was nitrided under ammonia gas at 700 ℃ for 3 hours to obtain Cs 0.007 Ce 0.1 -CoMoO x -N catalyst was prepared. At this time, the above Cs 0.007 Ce 0.1 -CoMoOx - In catalyst notation, the subscript indicates the moles of the corresponding component.

[0106] <Experimental Example 1: Measurement of Ammonia Decomposition Reaction According to Catalyst Aging Conditions>

[0107] In order to measure the effect of aging time on the ammonia decomposition reaction as a catalyst for the ammonia decomposition reaction, the ammonia conversion rate for the ammonia decomposition reaction was measured using the catalyst prepared in the preparation example, and the results are shown in Figure 1.

[0108] In the above Figure 1, Figure 1(a) is a graph showing the ammonia conversion rate according to the ammonia decomposition reaction temperature according to the aging time, and Figure 1(b) is a graph showing the ammonia conversion rate according to the ammonia decomposition reaction temperature according to the aging temperature.

[0109] At this time, the ammonia decomposition reaction was measured at atmospheric pressure in a quartz fixed-bed continuous flow straight-tube reactor equipped with a thermocouple. The reactor was provided with a quartz surface layer, and 0.1 g of the catalyst sample prepared in the preparation example was loaded thereon, followed by 6,000 mL / g cat. Pure NH3 (30 mL / min) was introduced into the reactor at a gas hourly space velocity (GHSV) of 1 / h.

[0110] Catalytic activity was evaluated in 50°C increments within a temperature range of 300°C to 600°C (60 minutes at each temperature). The concentration of the outlet gas was monitored using an online gas chromatograph (YL6500GC, YL Instrument Co., Korea) equipped with a thermal conductivity detector (TCD) and Porapak-N and Molesieve 13X columns. Ammonia conversion rate X NH3 (%) was calculated using Equation 1. In Equation 1 below, (NH3) in is the ammonia concentration entering the reactor, and (NH3) out is the ammonia concentration discharged from the reactor.

[0111] X NH3 (%)={[(NH3)in -(NH3) out ] / (NH3) in}× 100 ....(1)

[0112] As shown in Figure 1, there was no significant difference in the ammonia conversion rate according to the aging time, but regarding the aging temperature, the catalysts of Preparation Examples 5 and 7 aged at 80 ℃ and 90 ℃ showed higher ammonia activity compared to the catalyst of Preparation Example 6.

[0113] <Experimental Example 2: Measurement of Ammonia Decomposition Reaction According to Catalyst Calcination Conditions>

[0114] In order to measure the effect of calcination conditions on the ammonia decomposition reaction as a catalyst for the ammonia decomposition reaction, the ammonia conversion rate for the ammonia decomposition reaction was measured using the catalyst prepared in the preparation example, and the results are shown in FIG. 2. At this time, the ammonia conversion rate for the ammonia decomposition reaction was measured in the same manner as in Experimental Example 1, and the results are shown in FIG. 2.

[0115] As shown in Figure 2, the catalyst of Preparation Example 5, prepared through first and second calcination, was found to have higher ammonia activity compared to the catalysts of Preparation Examples 8 to 11, prepared through calcination at a single temperature or without calcination.

[0116] <Experimental Example 3: Measurement of Ammonia Decomposition Reaction According to Catalyst Nitriding Treatment Conditions>

[0117] In order to measure the effect of nitriding treatment conditions on the ammonia decomposition reaction as a catalyst for the ammonia decomposition reaction, the ammonia conversion rate for the ammonia decomposition reaction was measured using the catalyst prepared in the preparation example, and the results are shown in Figure 3.

[0118] In the above Figure 3, Figure 3(a) is a graph showing the ammonia conversion rate according to the ammonia decomposition reaction temperature according to the nitriding treatment time, and Figure 3(b) is a graph showing the ammonia conversion rate according to the ammonia decomposition reaction temperature according to the nitriding treatment temperature.

[0119] At this time, the ammonia conversion rate for the ammonia decomposition reaction was measured in the same manner as in Experimental Example 1, and the results are shown in Fig. 3.

[0120] As shown in Figure 3, the catalysts of Preparation Examples 5, 12, and 13, which were prepared by nitriding for more than 2 hours, showed superior ammonia decomposition activity compared to the catalysts of Preparation Examples 15 and 14, which were prepared by not performing nitriding or by nitriding for 1 hour. Regarding the temperature of the nitriding treatment, the catalyst of Preparation Example 5, which was nitrided at 700 ℃, showed higher ammonia decomposition activity compared to the catalyst of Preparation Example 16, which was nitrided at 750 ℃.

[0121] <Experimental Example 4: Measurement of Ammonia Decomposition Reaction According to the Molar Ratio of Ce and Cs of the Catalyst>

[0122] To measure the effect of the ammonia decomposition reaction according to the molar ratio of cerium (Ce) and cesium (Cs) as catalysts for the ammonia decomposition reaction, the ammonia conversion rate for the ammonia decomposition reaction was measured using catalysts prepared with different amounts of cerium (Ce) and cesium (Cs) while keeping the content of cobalt and molybdenum nitride the same, in the same manner as in Experimental Example 1, and the results are shown in Figures 4 and 5.

[0123] In the above Figure 4, Figure 4(a) is a graph showing the ammonia conversion rate of catalysts prepared with different cerium (Ce) contents, Figure 4(b) is a graph showing the ammonia conversion rate of catalysts prepared with different cesium (Cs) contents, and Figure 5 is a graph showing the ammonia conversion rate of a cobalt and molybdenum composite nitride catalyst that does not contain cerium and / or cesium and a cobalt and molybdenum composite nitride catalyst that contains cerium and cesium.

[0124] As shown in FIG. 4(a), the catalysts prepared in Preparation Examples 5, 18, and 19 showed a higher ammonia conversion rate compared to catalysts that did not contain cerium (Preparation Example 23), or contained 0.01 mol (Preparation Example 17) and 0.50 mol (Preparation Example 20), even though the cesium content was the same. As shown in FIG. 4(b), the catalysts prepared in Preparation Examples 5, 21, and 22 showed a higher ammonia conversion rate compared to the catalyst in Preparation Example 24 that did not contain cesium, even though the cerium content was the same.

[0125] In addition, as shown in Fig. 5, the catalyst of Preparation Example 5 was found to have a higher ammonia conversion rate compared to catalysts that do not contain cerium or cesium (Preparation Examples 23 and 24) or catalysts that do not contain both cerium and cesium (Preparation Example 1).

[0126] <Experimental Example 5: Measurement of Long-term Stability of Catalyst>

[0127] To measure the long-term stability of a catalyst containing cerium and / or cesium as a catalyst for an ammonia decomposition reaction, the catalysts prepared in Preparation Examples 1 and 5 and Preparation Examples 23 to 24 were used to perform an ammonia decomposition reaction for 100 hours, and the long-term stability of the catalyst was measured, and the results are shown in FIG. 6.

[0128] In the above 6, Fig. 6(a) is a graph measuring the ammonia conversion rate according to reaction time, and Fig. 6(b) is the initial ammonia conversion rate (X 0 NH3 Ammonia conversion rate (X) that changed according to reaction time relative to ) NH3 This is a graph measuring ).

[0129] X NH3 / X 0 NH3 = Ammonia conversion rate over time / Initial ammonia conversion rate

[0130] The above measurements were taken for 100 hours at an ammonia space velocity of 54,000 ml / g cat. / h and an indicator temperature of 550 ℃ at atmospheric pressure, and the results are shown in Fig. 6 as an ammonia conversion rate.

[0131] As shown in Fig. 6, it was confirmed that the catalyst prepared in Preparation Example 5 maintained stable catalytic activity for 100 hours with a high conversion rate compared to Preparation Examples 1, 23 to 24.

[0132] <Experimental Example 6: Measurement According to Catalyst Preparation Method>

[0133] In order to measure the effect of the ammonia decomposition reaction according to the manufacturing method as a catalyst for the ammonia decomposition reaction, the ammonia conversion rate for the ammonia decomposition reaction at different temperatures was measured using the catalysts of Manufacturing Example 5 and Manufacturing Examples 25 to 28, which were manufactured with different manufacturing methods while keeping the content of cobalt and molybdenum nitride the same, in the same manner as Experimental Example 1, and the results are shown in Table 2.

[0134] [Table 2]

[0135]

[0136] As shown in Table 2, compared to the catalysts of Examples 5, 25, and 26 prepared by the precipitation method, it was confirmed that the catalyst performance of Examples 27 and 29 prepared by the solvent-deficient milling method using ball milling did not decrease even when the manufacturing scale increased.

[0137] Although the present invention has been described with reference to the embodiments described above, different embodiments may be constructed within the concept and scope of the invention. Accordingly, the scope of the invention is defined by the appended claims and their equivalents, and is not limited by the specific embodiments described in this specification.

Claims

Claim 1 A catalyst for an ammonia decomposition reaction with improved catalytic stability, characterized by containing both cesium and cerium in a cobalt and molybdenum complex nitride. Claim 2 A catalyst for an ammonia decomposition reaction with improved catalyst stability, characterized in that, in claim 1, the cesium is contained in an amount of 0.001 mol to 0.05 mol per 1 mol of cobalt and molybdenum complex nitride. Claim 3 A catalyst for an ammonia decomposition reaction with improved catalyst stability, characterized in that, in claim 1, the cerium is contained in an amount of 0.01 mol to 0.4 mol per 1 mol of cobalt and molybdenum complex nitride. Claim 4 A catalyst for an ammonia decomposition reaction with improved catalyst stability, characterized in that, in the cobalt and molybdenum composite nitride according to claim 1, the cobalt is contained in an amount of 0.5 mol to 1.5 mol per 1 mol of molybdenum. Claim 5 A method for producing a catalyst for an ammonia decomposition reaction with improved catalyst stability, characterized by comprising: (a) a step of mixing a cobalt precursor, a molybdenum precursor, a cesium precursor, and a cerium precursor; (b) a step of drying the mixture from step (a); and (c) a step of nitriding the mixture dried in step (b) with a nitrogen source to produce a cobalt and molybdenum composite nitride containing both cesium and cerium. Claim 6 A method for producing a catalyst for an ammonia decomposition reaction with improved catalyst stability, characterized in that, in claim 5, the method includes a step of aging the mixture of step (a) after step (a). Claim 7 A method for preparing a catalyst for an ammonia decomposition reaction with improved catalyst stability, characterized in that, in claim 6, the aging is performed at 25 ℃ to 100 ℃ for 0.1 hours to 10 hours. Claim 8 A method for manufacturing a catalyst for an ammonia decomposition reaction with improved catalyst stability, characterized in that, in claim 5, the above step (b) further includes a step of calcining after drying. Claim 9 A method for manufacturing a catalyst for an ammonia decomposition reaction with improved catalyst stability, wherein, in claim 8, the above calcination is characterized by performing a first calcination at 100 ℃ to 400 ℃, followed by a second calcination at 400 ℃ to 700 ℃. Claim 10 A method for preparing a catalyst for an ammonia decomposition reaction with improved catalyst stability, wherein, in claim 5, the mixing in step (a) above utilizes solvent-deficient milling. Claim 11 A method for producing hydrogen from ammonia, characterized by contacting a cobalt and molybdenum complex nitride containing both cesium and cerium with a gas containing ammonia to cause an ammonia decomposition reaction. Claim 12 A method for producing hydrogen from ammonia according to claim 11, characterized in that the contact between the ammonia and the cobalt and molybdenum complex nitride containing cesium and cerium is performed at 300 ℃ to 600 ℃.

Citation Information

Patent Citations

  • Catalyst for Decomposing Ammonia and Method for Generating Hydrogen Using the Same

    KR1020220034652A

  • Catalyst for production of hydrogen and process for producing hydrogen using the catalyst, and catalyst for combustion of ammonia, process for producing the catalyst, and method for combustion of ammonia using the catalyst

    KR1020110129394A